Fuel Cells applied in Vehicles (FCV’s) - Sumitha Meyappan. (2012)
Today, there is an increase in energy and power generation demand. Fuel cells have been widely recognized as one of the most promising green technologies to meet power generation demands. With the creation of Fuel cell vehicles (FCVs), this can help to reduce greenhouse gases and other pollutions which are emitted by the Internal Combustion Engines (ICEs).